Identification of structural variation in mouse genomes - Keane, Thomas M.; Wong, Kim; Adams, David J.; Flint, Jonathan; Reymond, Alexandre; Yalcin, Binnaz (Frontiers in Genetics, 2014)
Traditionally, the identification of structural variation in genomes has been challenging. However, with the recent advances in high-throughput DNA sequencing and paired-end mapping (PEM) methods, the ability to identify structural variation and their respective association to human diseases has improved considerably. In this review, we describe our current knowledge of structural variation in the mouse, one of the prime model systems for studying human diseases and mammalian biology. We further present their evolutionary implications on transposable elements. We conclude with future directions on the study of structural variation in mouse genomes that will increase our understanding of their architecture and functional consequences.